Design of Backhoe Arm Prototype with Arduino Uno Microcontroller Based Hydraulic System - Riswan E. W. Susanto; Saiful Arif (Universitas Trunojoyo Madura, 2022)
Hydraulic is the use of fluid to move power from one point to another. In the hydraulic system the fluid used is fluid in the same liquid form as used in the old system. Fluid in the hydraulic system will continue the pressure from the hydraulic pump to the piston on the hydraulic cylinder. In the design of hydraulic systems, the props of prototype Backhoe arm carrying capacity of 1 kg of the hydraulic system are used to move the arms from the bucket, arm and boom. In planning mechanical manufacture on the excavator arm frame using a metal plate with a thickness of 3mm, using Fillet welding joints and bolt connection sizes M4 and M5. For planning the manufacture of transmission drive using a 12 V DC brushless motor with 150 W motor power, Shaft with a diameter of 18mm, bearings using the type of UCF 203, and planning a straight gear with 70, and:20 number of gears with a ratio of 35 rotation. Planning the calculation of excavator arm motion obtained results where the driving motor on the body (swing) rotates in a clockwise and counterclockwise direction to rotate 3600, rotational speed 11160 Nmm. In the Experiment Report the method used in designing the hydraulic system on the prototype Backhoe arm is to carry out a hydraulic system planning which includes power pack planning, valve planning, servo motor planning, and cylinder planning. Based on calculations, the planning of the pump head power pack has a pressure of 633,703.24 Pa and a hydraulic pump power of 0.165 HP. The results of the calculation of the hydraulic cylinder planning are the hydraulic cylinder pressure on the bucket of 0.0015 N / mm2, the pressure of the hydraulic cylinder on the arm of 0.0477 N / mm2, the pressure of the hydraulic cylinder on the boom of 0.159 N / mm2, and the flow of fluid flow on the hydraulic cylinder at 15,700 mm3 / second. The results of calculation of reservoir planning are reservoir dimensions of 0,00066 m3 and reservoir oil volume of 0.6 liters. The control system is used to control the brushless pump motor, brushed motor, servo valve. The control system uses the nRF24L01 module or with radio signal communication with a frequency of 2.4 GHz. In this control system there are transmitters and receivers, The transmitter functions to set point data from the joystick module and potentiometer that will be sent to the receiver, receiver functions as a receiver of data from the transmitter and serves to send signals to the brushed motor motor, and servo valve. From the results of testing the data transmission control system with the nRF24L01 module running well with conditions blocked by 3 walls